1982
DOI: 10.1056/nejm198211113072002
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Chromosomal Abnormalities in Histologic Subtypes of Non-Hodgkin's Lymphoma

Abstract: Using a new high-resolution technique for chromosomal analysis, we have successfully studied biopsy specimens of lymph nodes from 42 of 44 patients with non-Hodgkin's lymphoma and have categorized them using the new international histologic formulation and immunologic markers. Abnormalities of the clonal chromosomes were detected in all 42 patients. Three recurrent chromosomal aberrations were found to correlate with certain histologic types: a translocation between chromosomes 18 and 14 in 16 of 19 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
173
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 593 publications
(179 citation statements)
references
References 18 publications
6
173
0
Order By: Relevance
“…In the intermediategrade patients we found bcl-2/JH rearrangements in approximately 34% of bone marrow and peripheral blood samples. This finding is consistent with other studies reporting an overall frequency of approximately 20%-40% of the t(14;18) in this group of patients (Yunis et al, 1982;Lee et al, 1987a;Aisenberg et al, 1988;Yunis et al, 1989;Lambrechts et al, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the intermediategrade patients we found bcl-2/JH rearrangements in approximately 34% of bone marrow and peripheral blood samples. This finding is consistent with other studies reporting an overall frequency of approximately 20%-40% of the t(14;18) in this group of patients (Yunis et al, 1982;Lee et al, 1987a;Aisenberg et al, 1988;Yunis et al, 1989;Lambrechts et al, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 85% of FL patients and one-third of patients with diffuse large-cell lymphoma (DLCL) carry the t(14;18) (q32;q21) translocation in tissue specimens, as judged by cytogenic and molecular studies (Yunis et al, 1982;Lee et al, 1987a;Weiss et al, 1987;Ngan et al, 1988;Aisenberg et al, 1988). This translocation results in the juxtaposition of the bcl-2 protooncogene located on chromosome 18 with the immunoglobulin heavy chain gene (JH) on chromosome 14 (Tsujimoto et al, 1984;Bakhshi et al, 1985;Cleary et al, 1986a).…”
mentioning
confidence: 99%
“…Unlike the features of follicular neoplasms, where compartmentalization of TH cells (Tubbs et al, 1983) and "NK cells" (Tubbs et al, 1983; occur within the follicular lesions, both TH cells and Leu7+ cells occur as apparent random elements in MLL . T cells are not of the malignant clone in B-CLL (Gharton et al, 1980;Yunis et al, 1982;Fialkow et al, 1978). T suppressor cells in our study were most commonly in the spleen, as others have shown (Kay et al, 1982 …”
Section: Discussionsupporting
confidence: 76%
“…FLs are characterized by the t(14;18)(q32;q21), 7,8 which juxtaposes the BCL-2 gene on chromosome 18 with the immunoglobulin heavy chain gene locus on chromosome 14, resulting in constitutive expression of bcl-2 protein. [9][10][11][12][13][14][15] Bcl-2 protein is antiapoptotic, leading to the accumulation of follicular B cells that might otherwise be eliminated by programmed cell death.…”
Section: Introductionmentioning
confidence: 99%